2017
DOI: 10.4269/ajtmh.16-0901
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome of Toxoplasma gondii Infected Host Cells Reveals Specific Cellular Processes Predominating in Different Phases of Infection

Abstract: The invasion of tachyzoites into the host cell results in extensive host cell signaling activation/deactivation that is usually regulated by the phosphorylation/dephosphorylation. To elucidate how regulates host cell signal transduction, the comparative phosphoproteome of stable isotope labeling with amino acids in cell culture-labeled human foreskin fibroblast cells was analyzed. The cells were grouped (Light [L], Medium [M], and Heavy [H] groups) based on the labeling isotope weight and were infected with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Interestingly, host cell vimentin was found to interact with Tg ROP18 in our previous protein interaction screening based on BiFC, and the results of this study verified those findings further using FRET and Co-IP experiments (Figure 6 ). In our previous phosphoproteinomics assays of T. gondii infected HFF cells, host cell vimentin exhibited a complex phosphorylation pattern at different infection times 34 . In this study, a dynamic phosphorylation pattern of vimentin was identified in host cells infected with T. gondii RH and RH Δ rop18 strains using phos-Tag assays, and the results indicated that the phosphorylation pattern of vimentin was partly affected by T. gondii ROP18; moreover, vimentin phosphorylated by Tg ROP18 was also demonstrated by our kinase assay in vitro (Figure 7 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, host cell vimentin was found to interact with Tg ROP18 in our previous protein interaction screening based on BiFC, and the results of this study verified those findings further using FRET and Co-IP experiments (Figure 6 ). In our previous phosphoproteinomics assays of T. gondii infected HFF cells, host cell vimentin exhibited a complex phosphorylation pattern at different infection times 34 . In this study, a dynamic phosphorylation pattern of vimentin was identified in host cells infected with T. gondii RH and RH Δ rop18 strains using phos-Tag assays, and the results indicated that the phosphorylation pattern of vimentin was partly affected by T. gondii ROP18; moreover, vimentin phosphorylated by Tg ROP18 was also demonstrated by our kinase assay in vitro (Figure 7 ).…”
Section: Discussionmentioning
confidence: 89%
“…The assembly and solubility of vimentin are regulated by the phosphorylation/dephosphorylation of vimentin at Ser38 and Ser55 induced by Rab7a 33 . Moreover, phosphorylation level of vimentin Ser38 was significantly upregulated in host cell infected with T. gondii at both 2h and 6h comparing to host cell without T. gondii infection 34 . Consistent with the above reports, higher vimentin expression corresponding to much lower solubility in host cell with T. gondii infection for 2h and 6h, which also suggest that vimentin phosphorylation is associated with its solubility.…”
Section: Discussionmentioning
confidence: 90%
“…Qualitative analysis indicated that 1061 and 984 proteins with 3735 and 3396 modified sites in RH and ME49 strain T. gondii , respectively, were crotonylated, and 1950 and 1720 proteins with 9502 and 8092 2-hydroxyisobutyrylation sites, respectively, in the two parasite strains were identified. In addition to the finding that modification of proteins was more prevalent in the RH strain than in the ME49 strain, lysine crotonylation and 2-hydroxyisobutyrylation were the most prominent PTMs in T. gondii except for phosphorylation (11, 12, 4957) (phosphorylation can occur on diverse amino acids) (supplemental Table S6), suggesting critical roles of crotonylation and 2-hydroxyisobutyrylation in the regulation of various biological processes of the parasites.…”
Section: Discussionmentioning
confidence: 95%
“…The dried peptides were reconstituted in a solution containing 65% (v/v) acetonitrile (ACN) and 3.5% (v/v) trifluoroacetic acid (TFA) and then saturated with glutamic acid. Phosphopeptides were enriched using TiO 2 , as previously described ( He et al, 2017a ). Briefly, iTRAQ-labeled peptides were added into the freshly prepared TiO 2 beads (GL Sciences) at peptides-to-beads ratio of 1:4 (mass/mass) and then incubated for 20 min at 37°C with end-over-end rotation.…”
Section: Methodsmentioning
confidence: 99%